Agronomic performance and genetic gain by selection of physic nut in three Brazilian regions - Laviola, Bruno Galvêas; Silva, Sergio Delmar dos Anjos e; Juhász, Ana Cristina Pinto; Rocha, Rodrigo Barros; Oliveira, Reriton Joabél Pires de; Albrecht, Julio Cesar; Alves, Alexandre Alonso; Rosado, Tatiana Barbosa (Pesquisa Agropecuaria Brasileira, 2014)
The objective of this study was to evaluate the agronomic performance and genetic gain by the selection of half‑sib families of physic nut grown in three Brazilian regions. Based on previous phenotypic selection, three progeny tests were performed, in 2008, in the municipalities of Planaltina, DF, Nova Porteirinha, MG, and Pelotas, RS. A randomized complete block design was used, with three replicates, and five plants per plot. Randomly collected seeds from a population without selection were used as control. There was a significant interaction between the effects of genotypes and environments. Estimates of variance components and genetic parameters indicated that it is possible to obtain genetic gains from selection of the best families in the evaluated environments. In each environment, at least one family was selected with a higher performance than the control treatment. Mass selection in the three environments provided 72% of genetic gains. The agronomic performance had a high correlation coefficient between the environments of Planaltina and Nova Porteirinha, which did not occur in Pelotas. Genotype x environment interaction should be considered in the recommendations of physic nut genetic material for different environments.